Compliant grasp in a myoelectric hand prosthesis. - Okuno, R.
A novel myoelectric hand prosthesis consisting of electromyogram (EMG) signal processing units, a microprocessor-based dc motor servo system, and a 1 degree-of-freedom (DOF) end effector has been developed. The flexion angle and compliance of the finger of this prosthesis can be voluntarily controlled with EMG signals. The biomimetic controller for the myoelectric hand incorporated a model of the neuromuscular control system constructed from an analysis of the force response to length perturbation of the flexor pollicis longus muscle, processing of EMG signals, and the configuration of the hand. Basic functions of the human neuromuscular control system are realized by using position control, force feedback, and variable gain, modulated by EMG signal amplitude. A limb-absent person and four healthy subjects were able to voluntarily control the finger angle and compliance of the prosthesis and were able to easily grasp a soft object after a short training period.
Keywords: Biomimetic controller; Electromyogram signal processing units; End effector; Finger compliance; Flexion angle; Flexor pollicis longus muscle; Force feedback; Microprocessor-based dc motor servo system; Myoelectric hand prosthesis; Neuromuscular control system; Position control